(untitled) (Acta Judicial Journal, 2019)
The judicial administration counsellor, as first-order juridical operators within the scope of the process (authentic "caretakers of the process" in the fortunate words of Jesús Seoane Cacharrón) cannot be unaware of the important novelties and advances that have taken place in the recent times in the foreclosure, especially as a result of the positive influence of the jurisprudence of the TJUE and the required legal reforms that it has demanded and entailed. Moreover, the thesis that is sustained in this article, which I will try to defend with objective arguments, is that the judicial counsellor can and should take a step forward making a progressive interpretation of the procedural rules , in line with the theses defended by the DGRyN (Registers and notarial General Direction) and a growing part of the jurisprudence, to try to protect the debtor-consumer in everything that is within their reach, and this with total independence of the criterion that other instances of decision can support in the process. Because the judicial counsellors are not mere automatons applying the procedural law, but qualified interpreters of it and, therefore, the first line of defense of the debtor-consumer against the performance of the powerful, predisposing employer.